The AVERT MoCA Data: Scoring Reliability in a Large Multicenter Trial. (July 2020) - Cumming, Toby B.; Lowe, Danielle; Linden, Thomas; Bernhardt, Julie
The Montreal Cognitive Assessment (MoCA) is a widely used cognitive screening tool in stroke. As scoring the visuospatial/executive MoCA items involves subjective judgement, reliability is important. Analyzing data on these items from A Very Early Rehabilitation Trial (AVERT), we compared the original scoring of assessors ( n = 102) to blind scoring by a single, independent rater. In a sample of scoresheets from 1, 119 participants, we found variable interrater reliability. The match between original assessors and the independent rater was the following: trail-making 97% (κ = 0.94), cube copy 90% (κ = 0.80), clock contour 92% (κ = 0.49), clock numbers 89% (κ = 0.67), and clock hands 72% (κ = 0.46). For all items except clock contour, the independent rater was "stricter" than the original assessors. Discrepancies were typically errors in original scoring, rather than borderline differences in subjective judgement. In trials that include the MoCA, researchers should emphasize scoring rules to assessors and implement independent data checking, especially for clock hands, to maximize accuracy.